2022
DOI: 10.1101/2022.04.11.22273744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A meta-epidemiological assessment of transparency indicators of infectious disease models

Abstract: Mathematical models have become very influential, especially during the COVID-19 pandemic. Data and code sharing are indispensable for reproducing them, protocol registration may be useful sometimes, and declarations of conflicts of interest (COIs) and of funding are quintessential for transparency. Here, we evaluated these features in publications of infectious disease-related models and assessed whether there were differences before and during the COVID-19 pandemic and for COVID-19 models versus models for o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…This information allowed a correction of the estimates of the proportion of articles that satisfy each of the transparency indicators. As in previous work(11), the corrected proportion C(i) of publications satisfying an indicator i was obtained by U(i) × TP + (1 − U(i)) × FN, where U(i) is the uncorrected proportion detected by the automated algorithm, TP is the proportion of true positives (proportion of those manually verified to satisfy the indicator among those identified by the algorithm as satisfying the indicator), and FN is the proportion of false negatives (proportion of those manually found to satisfy the indicator among those categorized by the algorithm not to satisfy the indicator).…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…This information allowed a correction of the estimates of the proportion of articles that satisfy each of the transparency indicators. As in previous work(11), the corrected proportion C(i) of publications satisfying an indicator i was obtained by U(i) × TP + (1 − U(i)) × FN, where U(i) is the uncorrected proportion detected by the automated algorithm, TP is the proportion of true positives (proportion of those manually verified to satisfy the indicator among those identified by the algorithm as satisfying the indicator), and FN is the proportion of false negatives (proportion of those manually found to satisfy the indicator among those categorized by the algorithm not to satisfy the indicator).…”
Section: Methodsmentioning
confidence: 59%
“…In a previous evaluation (11) we had studied 1338 articles from 2019 and 2021 and we had showed that approximately a quarter of publications shared code, and a modestly higher proportion shared data in studies of infectious disease modelling. High rates of conflict of interest and funding disclosures were also observed in the same study (around 90% for both).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 216 articles, full-text articles were retrieved for all papers, and 70 were adjudicated as eligible for the review. Furthermore, the additional searches revealed another 44 eligible reports for inclusion, resulting in a total of 114 eligible meta-research studies examining a combined total of 2,254,031 primary articles for the review [8][9][10][11][12][13][14][15].…”
Section: Study Selection and Ipd Retrievalmentioning
confidence: 99%
“…Perhaps they do not even deserve to be seen as “studies”, but more as semi-formal speculations. This does not mean, however, that models should be discarded or that there is no room for improvement in terms of their transparency and validation ( Zavalis and Ioannidis, 2022 ). Medley (2022) presents an insider view of the difficulties and challenges that arose as models had to be produced, run, interpreted and applied in the UK in real time under critical circumstances.…”
mentioning
confidence: 99%